The Sierra Leone Teachers Union: Labor in a Post-Conflict Society - Amman, John; O'Donnell, James (WorkingUSA, 2011)
The Sierra Leone Teachers Union (SLTU) has long played an important role in the country's education system and its labor movement. With more than 30,000 members, the SLTU is the largest and perhaps the most powerful union in Sierra Leone today. Nonetheless, the union struggles with challenges unheard of in developed countries. It represents teachers in an education system that was ravished by its eleven-year civil war (1991 to 2002). Not only are working conditions extremely difficult for teachers (classroom overcrowding, lack of educational materials, low pay, and often late pay), the union must negotiate union agreements with the Ministry of Education, which itself has no direct influence on the nation's coffers. Sierra Leone's Ministry of Finance and more importantly, the International Monetary Fund set policies that directly impact the quality of Sierra Leone's education system and its teachers.

Sierra Leone Teaching Service Commission Act - Government of Sierra Leone (2011)